Changes in secondary metabolites and essential oil contents in black cumin (Nigella sativa L.) in response to drought stress - Yasemin Erdoğdu; Sıla Barut Gök; Erhan Göçmen (Journal of Applied Botany and Food Quality)
Water stress is one of the foremost stress factors affecting the production of secondary metabolites in plants. The aim of the research was to evaluate the response of black cumin (Nigella sativa L.) to water stress in terms of bioactive compounds and essential oil con- stituents in a semi-arid region (Thrace region, Türkiye). Black cumin seeds were subjected to six irrigation regimes (I0, I25, I50, I75, I100, I125). The total phenolic contents of extracts decreased significantly by about 0.39-0.59-fold under irrigation regimes from I75 to I125, compared to the drought stress conditions (I0). Irrigation regimes, except over-irrigation (I125) and low water deficit (I75) conditions, had no significant effect on the antioxidant activity. The highest flavonoid content recorded under the over-irrigation regime was 406.6±4.6 mg QE g-1. The effect of irrigation on essential oil content was statistically significant. The lowest thymoquinone content was obtained under the drought stress conditions (I0), while the highest thymoquinone content was obtained from the high-water deficit conditions (I25). Based on principal component analysis, carvacrol and 4-terpineol were the most determinant compounds involved in adaptation to drought stress, and the most determinant component for low water stress was thymoquinone, which had the highest rate in the study.